Nazm Al-Qur'an: a viable tafsir methodology - Khan, Israr Ahmad (2010)
Hundreds of tafsÊr works have been produced by Muslim scholars with a view to making the message of the Qur’Én accessible to the mankind. These works represent various trends, different approaches, diverse methodologies, multifarious objectives, and numerous schools of thought. Consequently, different and, at times, mutually conflicting interpretations of the words of Allah has caused Muslims to feel confused and dejected. Interestingly, scholars who have applied one and the same methodology to unfold the truth of the divine speech have also miserably failed to maintain the unity of the message of the Qur’Én, and come up with uncompromisingly contradictory interpretations. This situation serves as an obvious indicator that there is something wrong in the methodology of interpretation of the Qur’an. In the twentieth century some Muslim scholars such as al-FarÉhÊ and IÎlÉÍÊ proposed and also practically demonstrated a new methodology of tafsÊr known as Nazm al-Qur’Én. To them, it is not merely an excellent miraculous feature of the Qur’an but also a methodology. Application of this methodology in the Qur’Énic tafsÊr leads to the unity of message in the Qur’an. This methodology may enable the commentators of the Qur’Én to develop various meanings of verses but there is no possibility of conflict among scholars while interpreting the Qur’Én in terms of ideas. This paper introduces NaÐm al-Qur’Én as a methodology of tafsÊr and apply it to sËrah al-Jumu‘ah for practical purpose.